A Study of the Changes in the Distribution and Mobility of Armenians in the Montreal Region, 1972-1979 - Chichekian, Garo (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1981)
The Armenian community in Canada is a rather small one numbering to no more than about 30 000. Like other small ethnic minorities and for various reasons, its study has been neglected by scholars in this field. During the last eight years (1972-1979), the most characteristic pattern of the distribution of the Armenians in the Montréal region has been the persistence of a corridor shaped area of residential concentration, even though the actual location of this concentration has shifted in a northward direction. This change has been attracted by the relocation and new locations of Armenian religious institutions and socio-cultural institutions associated with them, as well as by the desire of a segment of the community to reside in quiet residential areas, characterized by single-family and duplex type of dwellings, and often at a relatively short distance from the Armenian institutions.